2018
DOI: 10.3389/fnagi.2018.00012
|View full text |Cite
|
Sign up to set email alerts
|

Microglia Polarization, Gene-Environment Interactions and Wnt/β-Catenin Signaling: Emerging Roles of Glia-Neuron and Glia-Stem/Neuroprogenitor Crosstalk for Dopaminergic Neurorestoration in Aged Parkinsonian Brain

Abstract: Neuroinflammatory processes are recognized key contributory factors in Parkinson's disease (PD) physiopathology. While the causes responsible for the progressive loss of midbrain dopaminergic (mDA) neuronal cell bodies in the subtantia nigra pars compacta are poorly understood, aging, genetics, environmental toxicity, and particularly inflammation, represent prominent etiological factors in PD development. Especially, reactive astrocytes, microglial cells, and infiltrating monocyte-derived macrophages play dua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
122
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 70 publications
(123 citation statements)
references
References 232 publications
(451 reference statements)
1
122
0
Order By: Relevance
“…Other studies, however, showed no difference in proliferation or differentiation of newborn cells in the SGZ of the DG after DAergic lesions (Ermine et al, and refs therein). As different factors including age, sex, inflammation, the brain region examined, and the post‐injury interval considered, significantly affect the NSC response to injury (Figure ; and Figure S1) (Khan, Wakade, de Sevilla, Brann, ; L'Episcopo, , ; L'Episcopo, Tirolo, Serapide, et al, ; Tatar, Bessert, Tse, Skoff, , and following sections), it seems plausible that impairment of SVZ and SGZ neurogenesis in PD may well depend on both DAergic and non‐DAergic related mechanisms.…”
Section: Wnt/β‐catenin Signalling In Pdmentioning
confidence: 99%
See 4 more Smart Citations
“…Other studies, however, showed no difference in proliferation or differentiation of newborn cells in the SGZ of the DG after DAergic lesions (Ermine et al, and refs therein). As different factors including age, sex, inflammation, the brain region examined, and the post‐injury interval considered, significantly affect the NSC response to injury (Figure ; and Figure S1) (Khan, Wakade, de Sevilla, Brann, ; L'Episcopo, , ; L'Episcopo, Tirolo, Serapide, et al, ; Tatar, Bessert, Tse, Skoff, , and following sections), it seems plausible that impairment of SVZ and SGZ neurogenesis in PD may well depend on both DAergic and non‐DAergic related mechanisms.…”
Section: Wnt/β‐catenin Signalling In Pdmentioning
confidence: 99%
“…Astrocyte dysfunctions with age and neurodegeneration are well recognized processes leading to a marked downregulation of astrocyte's supportive, neuroprotective and pro‐neurogenic properties (Barkho et al, ; Jiao & Chen, ; L'Episcopo, Tirolo, Peruzzotti‐Jametti, et al, ; L'Episcopo, Tirolo, Serapide, et al, ; Marchetti & Abbracchio, ; Marchetti et al, ; Sousa‐Victor et al, ; Yang et al, ). Within the SVZ niche, astrocyte dysfunction as a consequence of age and exposure to the PD neurotoxin was shown to inhibit both proliferation and neuroblast formation, as observed both in vivo and in vitro.…”
Section: The Influence Of Aging On Wnt/β‐catenin Signalling In the Comentioning
confidence: 99%
See 3 more Smart Citations